Cost control systems in the construction industry - Aspiras, Felix Fernandez; Scott, David; Jearkjirm, Vithool; Pama, Ricardo P.; Government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1978)
This study has been made to develop a simple but adequate cost control model which is presented in such a way as to help the small contractor and the manager establish a cost control system in their own construction companies. The existing concepts of cost control and the systems used by different writers are reviewed. An attempt is made to evaluate cost control in current practice by making inquiries to sever al construction firms. A general application of the model is presented. This will serve as an outline of the system and is applicable to a variety of projects. The model is applied to a specific project which is being constructed by a company without a cost control system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Construction industry -- Costs